2004
DOI: 10.1029/2003pa000921
|View full text |Cite
|
Sign up to set email alerts
|

Stability of North Atlantic water masses in face of pronounced climate variability during the Pleistocene

Abstract: [1] Geochemical profiles from the North Atlantic Ocean suggest that the vertical d 13 C structure of the water column at intermediate depths did not change significantly between glacial and interglacial time over much of the Pleistocene, despite large changes in ice volume and iceberg delivery from nearby landmasses. The most anomalous d 13 C profiles are from the extreme interglaciations of the late Pleistocene. This compilation of data suggests that, unlike today (an extreme interglaciation), the two primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
191
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 82 publications
(94 reference statements)
12
191
0
2
Order By: Relevance
“…The classic picture that has evolved since the work of Boyle and Keigwin (1987) and Duplessy et al (1988) is one of the present interglaciation as having little to no d 13 C gradient, reflecting the penetration of NADW to the abyss, versus the LGM 21 ka having a positive d 13 C gradient, suggesting that the North Atlantic was stratified with a divide at $2000 m separating enriched Glacial North Atlantic Intermediate Water from underlying depleted CDW. The Raymo et al (2004) analysis, however, found that glacial-interglacial d 13 C gradients over the last 1800 kyr often differed from this picture, with the most recent examples being relatively unique. Instead, the ''typical'' vertical d 13 C gradient, characteristic of both glaciations and interglaciations, is negative, implying a source of depleted d 13 C water in the North Atlantic.…”
Section: Article In Pressmentioning
confidence: 88%
See 4 more Smart Citations
“…The classic picture that has evolved since the work of Boyle and Keigwin (1987) and Duplessy et al (1988) is one of the present interglaciation as having little to no d 13 C gradient, reflecting the penetration of NADW to the abyss, versus the LGM 21 ka having a positive d 13 C gradient, suggesting that the North Atlantic was stratified with a divide at $2000 m separating enriched Glacial North Atlantic Intermediate Water from underlying depleted CDW. The Raymo et al (2004) analysis, however, found that glacial-interglacial d 13 C gradients over the last 1800 kyr often differed from this picture, with the most recent examples being relatively unique. Instead, the ''typical'' vertical d 13 C gradient, characteristic of both glaciations and interglaciations, is negative, implying a source of depleted d 13 C water in the North Atlantic.…”
Section: Article In Pressmentioning
confidence: 88%
“…Instead, the ''typical'' vertical d 13 C gradient, characteristic of both glaciations and interglaciations, is negative, implying a source of depleted d 13 C water in the North Atlantic. Raymo et al (2004) speculate that such a source was from brine formation beneath permanent sea ice covering the Norwegian-Greenland Seas, with depleted d 13 C values reflecting an attendant reduction in air-sea exchange.…”
Section: Article In Pressmentioning
confidence: 99%
See 3 more Smart Citations